Faktor Yang Mempengaruhi Harga Saham Dengan Profitabilitas Sebagai Pemoderasi Pada Perusahaan Pertambangan - Nuraini, Arisma; Hidayah, Nur (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Company value is used by investors to measure the level of performance of a company as seen from the stock price. The purpose of this study is to determine Corporate social responsibility and capital structure on stock prices with profitability as a moderation. The population of this study were mining companies listed on the Indonesian Stock Exchange for the period 2021-2023 with a sample of 23 companies. The sampling technique used the purposive sampling method with certain criteria. Data analysis used classical assumption tests, multiple regression tests and moderating regression analysis. The results of this study indicate that Corporate social responsibility has a significant positive effect on stock prices. Capital structure has no effect on stock prices. And profitability as a moderating variable is unable to moderate the relationship between Corporate social responsibility and capital structure on stock prices